2019
DOI: 10.21608/jenvbs.2019.11933.1058
|View full text |Cite
|
Sign up to set email alerts
|

Comprative study on rice germination and seedling growth under salinity and drought stresses

Abstract: R ICE is very important crop in Egypt and the production of rice yield faced many challenges such as, saline soil and drought. For salinity about 30% of lands affected by salinity specially northern part of delta, besides, in Egypt the people increase continuously but the water sources are constant so year by year the problem increase. The rice cultivars differed in salinity and drought tolerance in the various stages of plant life, so, study of rice tolerance in germination and seedling stage play a vital rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Concerning potassium content, the best genotype was the cross GAB-A/Giza179 under normal, salinity conditions. Some authors like, Zayed et al, (2010Zayed et al, ( ,2014Zayed et al, ( and 2017; Negm (2012 and2016); El-Mowafi et al, (2019 and2022) and Mazal et al, (2021) mentioned similar findings.…”
Section: The Most Desirable Mean Values For Mean Performancementioning
confidence: 72%
See 1 more Smart Citation
“…Concerning potassium content, the best genotype was the cross GAB-A/Giza179 under normal, salinity conditions. Some authors like, Zayed et al, (2010Zayed et al, ( ,2014Zayed et al, ( and 2017; Negm (2012 and2016); El-Mowafi et al, (2019 and2022) and Mazal et al, (2021) mentioned similar findings.…”
Section: The Most Desirable Mean Values For Mean Performancementioning
confidence: 72%
“…Rice is a very important crop in Egypt and the production of rice yield is facing several challenges such as saline soil and drought. Furthermore, about 30% of lands in northern part of delta are salt affected soil (Negm et al, 2019). Accordingly, salinity considered one of the major abiotic stresses affecting rice sustain-ability and yield.…”
Section: Introductionmentioning
confidence: 99%
“…The estimates of genetic parameters including coefficient of variation and heritability deserve attention in deciding selection criteria for improvement in the concerned characters. Estimates of genotypic variance (σ 2 g), phenotypic variance (σ 2 p), genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV) and broad sense heritability (H 2 ) are shown in Table 6 and Tuhina- Khatun et al, (2015) and Negm et al, (2019), who reported that genetic variance (𝜎 2 g) was higher than the environmental variance (𝜎 2 e). The phenotypic variance in a population is estimated using heritability analysis, which also quantify the relative contributions of genetic and non-genetic component differences.…”
Section: Estimates Of Genetic Parametersmentioning
confidence: 99%
“…Global climate change and intensive agricultural practices have exacerbated the impact of abiotic stresses such as drought, salinity, UV rays, low and high temperatures that increase soil and water salinity especially in arid and semiarid areas and act as limiting factors that hinder plant growth and decrease agricultural productivity by 20% and 50% [1].These stressed conditions of soil salinization have grown up in Egypt to represent about 46% of the total Nile Delta zone due to the complex environmental risks from climate change and human-caused developments in addition to water scarcity problems [2,3]. Nowadays in Egypt, there is a tendency to expand the cultivated area of many crops in Northeastern Delta of Egypt, including wheat and faba bean in newly-reclaimed soil, Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%